Ocular toxicity of Anti-Tubercular drugs - Ritika Aggarwal; Prabhpreet Sethi; Ram Krishan Duvesh; Harinder Singh Sethi; Mayuresh Naik; Harminder K. Rai (Delhi Journal of Ophthalmology)
Tuberculosis is the most common cause of infectious disease-related mortality worldwide caused by Mycobacterium tuberculosis. Ethambutol (EMB) and isoniazid (INH) are synthetic first-line agents of the anti-tubercular treatment (ATT) against Mycobacterium tuberculosis. Ethambutol, though well tolerated, is known to cause optic neuritis, more specifically retro bulbar neuritis causing decreased visual acuity, central scotomas, and loss of red-green color vision. Isoniazid can rarely cause retro bulbar optic neuritis. Streptomycin is known to cause pseudotumor cerebri. Thioacetazone can produce severe hypersensitivity cutaneous reactions including Steven Johnson Syndrome affecting the skin and mucosa including conjunctiva. Optic neuropathy has been reported as a side effect of long-term use of linezolid. This is particularly seen in cases of drug resistant tuberculosis where treatment with linezolid may continue for about 18-24 months Educating the patients for early detection of the ocular manifestations and regular follow-ups are very essential. The purpose of this review is to update the clinicians on the ocular side effects of anti tubercular drugs and the type of eyecare to be provided to the patients treated with these medications.